2011
DOI: 10.1007/s00280-011-1572-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liposomal cisplatin versus cisplatin in non-squamous cell non-small-cell lung cancer

Abstract: PurposeLiposomal cisplatin was developed to reduce the systemic toxicity of cisplatin, particularly the nephrotoxicity, and it has been used in combination with other agents in pancreatic and head and neck cancers and non-small-cell lung cancer (NSCLC). Our objective was to compare the effectiveness of lipoplatin combined with paclitaxel versus cisplatin with paclitaxel in advanced non-squamous NSCLC.MethodsDuring 2007–2010, 202 patients with non-squamous NSCLC (stage IIIB and IV) were recruited from the two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 31 publications
(25 reference statements)
1
48
0
Order By: Relevance
“…As this liposomal formulation is less toxic, preclinical and clinical studies made on NSCLC have shown that a 3-6 times higher dose than the standard dose of cisplatin resulted to a better anticancer effect with lower toxicity [24,25]. In our studies, no toxicity was observed with Lipoplatin ™ as measured by the mean survival time of the animals compared to controls, whatever the route of administration used.…”
Section: Discussionsupporting
confidence: 39%
“…As this liposomal formulation is less toxic, preclinical and clinical studies made on NSCLC have shown that a 3-6 times higher dose than the standard dose of cisplatin resulted to a better anticancer effect with lower toxicity [24,25]. In our studies, no toxicity was observed with Lipoplatin ™ as measured by the mean survival time of the animals compared to controls, whatever the route of administration used.…”
Section: Discussionsupporting
confidence: 39%
“…Due to their reactive nature, most of the drugs are rapidly inactivated by binding to proteins or other molecules upon entering the organism and never reaching the tumor in an active form that is considered a major cause of much dose-limiting toxicity [39]. One approach to try and to circumvent these drawbacks is to encapsulate the drug in liposomes.…”
Section: +mentioning
confidence: 99%
“…Sterically stabilized lipospomal variants of doxorubicin and cisplatin are commercially available and have been shown to exhibit higher therapeutic efficacy or at least better tolerability than the free drugs. Both agents have so far been successfully tested against various solid tumors including breast cancer (Rivera 2003, O'Brien 2008), Kaposi's sarcoma (Coukell & Spencer 1997, Sharpe et al 2002, non-squamous non-small-cell lung cancer (Mylonakis et al 2009, Stathopoulos et al 2011, and pancreatic cancer (Stathopoulos et al 2006), among others. Recently, we have demonstrated an extraordinary uptake phenomenon of liposomes, specifically in adrenocortical tumor cells (Hantel et al 2010(Hantel et al , 2012.…”
Section: Introductionmentioning
confidence: 99%